ANALISIS KESALAHAN NEWMAN SISWA DALAM MENYELESAIKAN SOAL NILAI MUTLAK DAN SCAFFOLDING-NYA - Budi, Bhakti Setya; Nusantara, Toto Nusantara; Subanji, Subanji Subanji; Susiswo, Susiswo Susiswo (Jurnal Pendidikan Matematika Undiksha, 2020)
This study aims to describe the types of errors made by students in solving questions of absolute value and scaffolding based on the Newman error analysis stage. The research method used is descriptive qualitative method. The research subjects are students of class X MA Miftahul Huda Kepanjen. Sampling with purposive sampling technique. Data obtained from the results of student tests, interviews and the scaffolding process. Based on the results of the study there were 81.25% reading errors, while transformation errors were 37.5%, and process skills were 28.13%. From this research it can be concluded that the types of mistakes made by students are reading inaccuracies, comprehension errors, transformation errors, process skill errors and encoding errors. While the form of scaffolding conducted is explaining, reviewing, restructuring and developing conceptual thinking